We help IT Professionals succeed at work.

# Proving trigonometry identities

on
Medium Priority
973 Views
Prove that   1  over 1-cosx   -      1 over 1+cosx  =   2cotxcscx
Comment
Watch Question

## View Solutions Only

CERTIFIED EXPERT
Most Valuable Expert 2014
Top Expert 2015
Commented:
1 /( 1-cosx)   -  1/( 1+cosx)
= (1+cosx)/((1+cosx)*(1-cosx)) - (1-cosx)/((1-cosx)*(1+cosx))

Not the solution you were looking for? Getting a personalized solution is easy.

Engineer
CERTIFIED EXPERT
Commented:
Hi,

1 /( 1-cosx)   -  1/( 1+cosx)
= (1 + cos x - 1 + cos x) / (1 - cos² x)
= 2cos x/sin² x
= 2(cos x/(sin x*sin x)
= 2(cos x/sin x)/sin x
= 2 tan x csc x

---
Harish
Commented:
1 /( 1-cosx)   -  1/( 1+cosx)

=

(1+cosx) - (1-cosx) all divided by (1-cosx)(1+cosx)

The numerator is 2cosx, the denominator 1-cos²x = sin²x

as cosx/sinx is cotx and 1/sinx is cscx, we get 2cotxcscx.

Q.E.D

Quite Easily Done.

BTW: This question is NOT worth 500 points. It looks anyway like home work and ought to be reduce to 50 points.
##### Thanks for using Experts Exchange.

• View three pieces of content (articles, solutions, posts, and videos)
• Ask the experts questions (counted toward content limit)
• Customize your dashboard and profile